Influence of voluntary pelvic floor muscle contraction and pelvic floor muscle training on urethral closure pressures: a systematic literature review. Issue 5 (May 2016) - Zubieta, Maria; Carr, Rebecca; Drake, Marcus; Bø, Kari
Abstract Introduction and hypothesis Stress urinary incontinence (SUI) is managed with pelvic floor muscle training (PFMT), but the mechanism of treatment action is unclear. Resting maximal urethral closure pressure (MUCP) is lower in women with SUI, but it is unknown whether PFMT can alter resting MUCP. This systematic review evaluated whether voluntary pelvic floor muscle (PFM) contraction increases MUCP above its resting value (augmented MUCP) and the effect of PFMT on resting and augmented MUCP. Methods Experimental and effect studies were identified using PubMed and PEDro. The PEDro scale was used to assess internal validity of interventional studies. Results We identified 21 studies investigating the influence of voluntary PFM contraction in women. Comparison was hindered by varying demographics, antecedent history, reporting of confirmed correct PFM contraction, and urethral pressure profilometry (UPP) techniques. Mean incremental increase in MUCP during PFM contraction in healthy women was 8–47.3 cm H2 O; in women with urinary incontinence (UI), it was 6–24 cm H2 O. Nine trials reporting MUCP as an outcome of PFMT were found. Wide variation in PFMT regimes affected the findings. Two studies found significant improvement in MUCP of 5–18 cm H2 0. Seven studies assessed augmentation of MUCP with PFM contraction; mean increase was −0.1 to 25 cm H2 0. Conclusions There is no definitive evidence that PFMT increases resting MUCP as its mechanism of action in managing SUI. The degree to which a voluntary PFM contraction augments MUCP varies widely. There was evidence to suggest PFMT increases augmented MUCP. Drawing firm conclusions was hampered by study methodologies.